Transcatheter closure of patent ductus arteriosus using duct occluder: an eleven-year experience from a single tertiary cardiac center - Sarkar, Achyut; Rani, Neha; Kumar, Prashant; Chaudhary, Shyam Sundar; Chatterjee, Suman (International Journal of Research in Medical Sciences, 2019)
Background: Patent Ductus Arteriosus (PDA) is a common congenital disorder. As an isolated lesion, PDA constitutes 6 to 11% of all congenital heart disease. PDA needs closure to eliminate pulmonary over circulation leading to volume overload of left ventricle, pulmonary vascular obstructed disease. Methods: This retrospective study was carried out in pediatric cardiology unit of Institute of Postgraduate Medical Education and Research, Kolkata from September 2005 to August 2016, which included 503 patients. Results: Device closure was attempted in 492 patient’s Procedural success was achieved in 85% cases on table, in who check aortogram revealed complete closure of PDA. In 15% cases, residual shunt was present. In 12% of cases, residual shunt disappeared during follow-up echocardiogram over 6-month follow-up. In 3% cases, small shunt remained at 6-month and 1-year follow up. Conclusion: Transcatheter closure of PDA by duct occluder is safe and effective with good mid-term outcome. The optimum assessment of ductul size and anatomy is crucial for optimum device size, which prevents residual shunt, device embolization and protrusion.